Thriving in a New Space of Virtual Homeroom Advising: A Phenomenological Inquiry - Lansangan, Ryan V.; Banzuelo, Hanilet C.; Saturno, Walner A.; Tiangsing, Evelyn T. (ASEAN Journal of Education, 2023)
Examining homeroom advisers’ experiences in the conduct of their migrated tasks in the online platform can help schools gauge teachers’ needs to move beyond the survival phase of the new educational delivery platform to a thriving phase that conforms to the demands of the new normal education. Relying on a phenomenological approach of inquiry, this study explored the meanings held by ten purposively selected Junior High School teachers on their experiences as homeroom advisers in the context of online education during the time of the COVID-19 pandemic. Thematic analysis revealed that the participants’ lived experiences could be dynamically described in spaces where they situate themselves in a new teaching platform. These spaces are termed as space for new opportunities as their perceptions towards the new normal education; space for flexibility in confronting the challenges; space for reflection and resiliency in exploring different coping strategies; space for creativity in establishing effective practices; and space for growth and professional learning in improving the quality of online advising. The study further concludes that becoming a homeroom adviser in the new normal involves situating themselves in these thriving spaces, which redirect their personal and professional identities as advisers in pursuing resilient and undisruptive teaching and learning.